PERAN PENANDA MOLEKULER PADA TERAPI GLIOMA - Rusdy Ghazali Malueka,* Yudiyanta,* Ahmad Asmedi* (NEURONA, 2017)
GLIOMAS ARE THE MOST COMMON PRIMARY CENTRAL NERVOUUS SYSTEM CNS TUMORS IN ADULTS NOWDAYS GLIOMA CLASSIFICATION HAS BEEN CHANGED FROM MORPHOLOGICAL BASED TO MOLECULAR BASED CLASSIFICATION